Effectiveness Of Recruitment and Position Mutations on Employee Achievement In Interior Contractor - Mega Sinta; Marselia Purnama; Adrian Hidayat Hidayat (Komunitas Dosen Indonesia, 2020)
Research using multiple linear analysis, correlation coefficient analysis, calculating the coefficient of determination, as well as testing the hypothesis by looking for the value of t count, then comparing t count with t table, and testing the hypothesis by looking for the calculated f value, then compares f count with f table. The results of the analysis obtained with the following details:From the results of multiple linear analysis, the equation Y = 1.392 + 0.349 X1 + 0.616 X2, and from the results of the correlation coefficient, job mutations have a positive and very strong correlation to the level of employee performance, which is 0.790, job mutations and recruitment have a positive and very positive correlation. strong on the level of employee performance that is equal to 0.850.Based on the results of the hypothesis test, the t-count for recruitment is 4.078, the t-count for work motivation is 9.241, with a t-table of 1.67722 obtained from the t-table distribution for df = 50 – 2 and the level of significance is 0.05. In other words, Ha is accepted and Ho is rejected, because t count > t table. Based on the hypothesis test for model 1, the f arithmetic result is 79.587, for model 2 the f arithmetic result is 61.067, with f table 1.45 with a significant level of 0.000, the number 0.000 < 0.05, thus Ho is rejected and Ha is accepted, because f count > f table